Virulence profiling of Shiga toxin-producing Escherichia coli recovered from domestic farm animals in Northwestern Mexico - Amézquita-López, Bianca A.; Quiñones, Beatriz; Lee, Bertram G.; Chaidez, Cristobal (Frontiers in Cellular and Infection Microbiology, 2014)
Shiga toxin-producing Escherichia coli (STEC) is a zoonotic enteric pathogen that causes human gastrointestinal illnesses. The present study characterized the virulence profiles of O157 and non-O157 STEC strains, recovered from domestic animals in small rural farms within the agricultural Culiacan Valley in Mexico. Virulence genes coding for adhesins, cytotoxins, proteases, subtypes of Shiga toxin (Stx), and other effectors were identified in the STEC strains by PCR. The genotyping analysis revealed the presence of the effectors nleA, nleB, nleE and nleH1-2, espK, and espN in the O157:H7 and O111:H8 STEC strains. Furthermore, the genes encoding the autoagglutinating adhesin (Saa) and subtilase (SubA) were exclusively identified in the O8:H19 eae-negative strains. The adhesin (iha) and the silent hemolysin (sheA) genes were detected in 79% of the O157 and non-O157 strains. To examine the relative toxicities of the STEC strains, a fluorescent Vero cell line, Vero-d2EGFP, was employed to measure the inhibition of protein synthesis by Stx. Analysis of culture supernatants from serotype O8:H19 strains with the stx gene profile stx1a, stx2a and stx2c and serotypes O75:H8 and O146:H8 strains with the stx gene profile stx1a, stx1c and stx2b, resulted in a significant reduction in the Vero-d2EGFP fluorescent signal. These observations suggest that these non-O157 strains may have an enhanced ability to inhibit protein synthesis in Vero cells. Interestingly, analysis of the stx2c-positive O157:H7 strains resulted in a high fluorescent signal, indicating a reduced toxicity in the Vero-d2EGFP cells. These findings indicate that the O157 and non-O157 STEC strains, recovered in the Culiacan Valley, display distinct virulence profiles and relative toxicities in mammalian cells and have provided information for evaluating risks associated with zoonotic STEC in this agricultural region in Mexico.